2017
DOI: 10.4103/nmj.nmj_289_16
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of breastfeeding: A comparative study of mothers in urban and rural communities of Lagos, Southwest Nigeria

Abstract: Background: Breastfeeding is a child survival intervention, which is effective in reducing child mortality. This study compared the knowledge, attitude, and practice of breastfeeding among mothers of under-five children in rural and urban communities of Lagos, Southwest Nigeria. Methods: This comparative cross-sectional study was conducted in Ikeja and Ikorodu, an urban and a rural local government area (LGA) of Lagos state, respectively. A total of 248 mothers of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
(26 reference statements)
4
13
1
Order By: Relevance
“…This finding was similar to that reported from a study done in India where 77% of the mothers discarded their colostrums [17]. It however differed from those reported from Saudi Arabia, UAE and Nigeria [16,18,19]. The poor awareness on the usefulness of colostrum in our study may be attributable to some negative myths surrounding the use of colostrum in many Nigerian cultures.…”
Section: Discussionsupporting
confidence: 86%
“…This finding was similar to that reported from a study done in India where 77% of the mothers discarded their colostrums [17]. It however differed from those reported from Saudi Arabia, UAE and Nigeria [16,18,19]. The poor awareness on the usefulness of colostrum in our study may be attributable to some negative myths surrounding the use of colostrum in many Nigerian cultures.…”
Section: Discussionsupporting
confidence: 86%
“…11 Balogun et al (75.8% rural versus 43.5% urban) initiated breastfeeding immediately after birth. 7 The present study showed that the practice of pre-lacteal feeding was observed to be prevalent in both urban and rural area mothers (21.3% urban and 22.7% mothers).…”
Section: Discussionmentioning
confidence: 48%
“…4 Balogun et al observed that the mothers in the urban area (84.7%) had correct knowledge of the usefulness of colostrum compared with 68.5% in the rural area. 7 Dhale et al study showed that 70% mothers had good knowledge. 8 The respondents with a good level of knowledge of breastfeeding in the urban and rural areas were 84.7% and 89.5%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Breastfeeding is a culturally accepted practice in many ethnic groups in Nigeria ( 9 , 18 , 19 ). Studies also indicate a high level of awareness and knowledge about breastfeeding among women in south west Nigeria ( 9 , 15 , 20 , 21 ). This may have been responsible for the high proportion of respondents who engaged in some form breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers in south west Nigeria reported exclusive breastfeeding rates ranging from 11% to 86.2% ( 9 , 15 , 32 ). The differences in study settings (urban or rural), the employment status and work demands of the women may be partly responsible for the wide variations in the rates of exclusive breastfeeding ( 2 , 9 , 20 ).…”
Section: Discussionmentioning
confidence: 99%